PERAN ARSIP DALAM PELINDUNGAN HAK-HAK KEPERDATAAN RAKYAT: Array - Khoerun Nisa Fadillah (Jurnal Kearsipan, 2013)
This research aims to analyze and describe the role of archives in civil rights protection. This is a descriptive qualitative research. Data collection used was literature. The technique of data analysis used was inductive analysis technique. The result showed important conclusions, namely: the role of archives in civil rights protection was as the main evidence being authentic and reliable, having function to meet the requirement of recognition of someone’s civil rights by the state untilbeing secured, and become a basic or source for a judge consideration in deciding civil suit.